Perencanaan Arsitektur Enterprise SI/TI pada SMA Negeri 1 Purwoasri Kediri menggunakan Kerangka TOGAF - Mohammad Haris Muzakki; Alva Hendi Muhammad (Sekawan Institut, 2025)
Digital transformation in the education sector requires institutions such as SMA Negeri 1 Purwoasri Kediri to adopt a structured and strategic approach in managing Information Systems and Information Technology (IS/IT). Fragmented systems, duplicated data, and inefficient services have become major challenges that hinder optimal performance and service delivery. This study aims to design an Enterprise Architecture (EA) using the TOGAF Architecture Development Method (ADM) framework to address these issues comprehensively. The research method combines observation, Focus Group Discussions (FGDs), and a structured analysis through TOGAF ADM phases—Preliminary, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. An evaluation of the institution’s current IS/IT condition was conducted using the EA Capability Maturity Model (EA-CMM) Scorecard. The results indicate that the school has a relatively strong foundation in IT governance (level 4/Managed), but still shows limitations in methodology usage, supporting tools, and human resource competencies, with an average score of 2.71 (Under Development). Business process mapping identified several priority systems, including student admission (PPDB), e-report cards, and digital libraries, alongside supporting systems such as inventory and asset management. The overall system effectiveness rate is 72.5%, these findings align with previous studies highlighting the urgency of integrated systems in schools. The study provides practical implications, including recommendations for phased implementation of EA, continuous training for human resources, and the development of an embedded EA model tailored to the needs and conditions of secondary educational institutions, ensuring sustainability and adaptability in the long term.